The main but not the accessory olfactory system is involved in the processing of socially relevant chemosignals in ungulates - KELLER, Matthieu; Lévy, Frédéric (Frontiers in Neuroanatomy, 2012)
Ungulates like sheep and goats have, like many other mammalian species, two complementary olfactory systems. The relative role played by these two systems has long been of interest regarding the sensory control of social behavior. The study of ungulate social behavior could represent a complimentary alternative to rodent studies because they live in a more natural environment and their social behaviors depend heavily on olfaction. In addition, the relative size of the main olfactory bulb (in comparison to the accessory olfactory bulb) is more developped than in many other lissencephalic species like rodents. In this review, we present data showing a clear involvement of the main olfactory system in two well-characterized social situations under olfactory control in ungulates, namely maternal behavior and offspring recognition at birth and the reactivation of the gonadotropic axis of females exposed to males during the anestrous season. In conclusion, we discuss the apparent discrepancy between the absence of evidence for a role of the vomeronasal system in ungulate social behavior and the existence of a developed accessory olfactory system in these species.